2009
DOI: 10.1093/ndt/gfp378
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide-generating pathways in haemodialysis patients: a study on relevant metabolites and transcriptional regulation of genes encoding for key enzymes

Abstract: Transcriptional deregulation of genes encoding for H(2)S-producing enzymes is present in uraemia. Although the specificity of the method employed for H(2)S detection is low, the finding that H(2)S is decreased is complemented by the lower sulphhaemoglobin levels. Potential implications of this study relate to the pathogenesis of the uraemic syndrome manifestations, such as hypertension and atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 42 publications
6
66
0
Order By: Relevance
“…The prediction would be that hydrogen sulfide generation is reduced in the kidney in diabetes. Previous studies have shown that plasma hydrogen sulfide level is lower in human subjects with type 2 diabetes (48,49) and in end stage kidney disease patients on hemodialysis (50). Relevant to diabetic kidney disease, hydrogen sulfide levels in the kidney are reduced in a chemical model of type 1 diabetes in the rat (8).…”
Section: Discussionmentioning
confidence: 98%
“…The prediction would be that hydrogen sulfide generation is reduced in the kidney in diabetes. Previous studies have shown that plasma hydrogen sulfide level is lower in human subjects with type 2 diabetes (48,49) and in end stage kidney disease patients on hemodialysis (50). Relevant to diabetic kidney disease, hydrogen sulfide levels in the kidney are reduced in a chemical model of type 1 diabetes in the rat (8).…”
Section: Discussionmentioning
confidence: 98%
“…Third, chronic administration of CSE inhibitor propargylglycine induces nephropathy. Finally, blood H 2 S and sulfhemoglobin levels, as well as CSE expression in blood mononuclear cells, are reduced in end-stage renal disease patients compared with healthy controls, indicating that chronic renal failure is a state of H 2 S deficiency (Perna et al, 2009). …”
Section: H 2 S Hypoxia and Chronic Kidney Diseasementioning
confidence: 99%
“…125 Red cell sulfhemoglobin (a putative marker of chronic H 2 S exposure) levels, is low in this patient population, and is accompanied by high plasma homocysteine and cysteine levels, with a significant negative correlation between cysteine and H 2 S. Gene expression of CSE in blood mononuclear cells is significantly lower, realizing a condition in which a transcriptional down-regulation of the gene encoding for a key H 2 S-producing enzyme is present. 126 These findings are in line with what was Figure 3.…”
Section: Ckd Progression and Complicationsmentioning
confidence: 83%